ANALISIS PELAYANAN KOPERASI CUBG TP.PAMULANG UNTUK MENINGKATKAN KEPUASAN ANGGOTA DENGAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ernima Gulo; Irvana Arofah; Ilmadi Ilmadi; Aden Aden; Gerry Sastro (LPPM Universitas Bina Bangsa, 2021)
This research was conducted to achieve improving the quality of service to members, for this reason, a service quality analysis method is needed. Here the methods needed are Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. The purpose of this study is to identify the level of customer satisfaction with service quality by the CUBG Tp Cooperative. Pamulang, to find out what aspects are supporting the improvement of service quality and to provide recommendations for improvements or revisions that are prioritized to improve service quality at the CUBG Tp Cooperative. Pamulang. This research method is quantitative descriptive analysis using Servqual and Importance Performance Analysis (IPA) methods. The results of this study are the level of satisfaction of cooperative members using the Customer Satisfaction Index (CSI) method with a percentage of 86.05%. Based on the calculation of Servqual Analysis of 5 dimensions, namely Tangibility (physical evidence), Reliability (Reliability), Responsiveness (Awareness / responsiveness), Assurance (Guarantee) and Empathy (Empathy) represented by 25 attributes obtained if members of the CUBG Cooperative TP.Pamulang have been satisfied with the Servqual provided by the CUBG Cooperative Tp.Pamulang, this is shown in the average gap between expectations and reality of 0.05